Determinación de los gases contaminantes en fuentes fijas en la parroquia Eloy Alfaro de la ciudad de Latacunga - Remachi Moreno, Jessica Noemi (2017)
This project was executed in Eloy Alfaro parish of Latacunga City, is based on the determination of the concentration of polluting gases that are produced in ducts of combustion at companies that are consider to study. It started with the identification of certain characteristics that must be met by the ducts to be monitored, the company ALCOPESA S.A. fulfill with the standards established in TULSMA, Book VI, Annex 3; such as; the sampling port and the scaffold that serves to place the lifeline and for mobility with the equipment. In this same phase of field and with the use of a GPS, researcher proceeded to have the exact point of the conduit having as coordinates UTM latitude 0764087; Length 9896921, in addition, a survey was carried out to the Head of maintenance of the steam generator, to know the combustible material used in their activities, the diameter and size of the ducts, with this it was confirmed that the conduit complies with the regulations of Book VI, Annex 3 of TULSMA, which in turn allows to determine the monitoring points, which for this research were four segments; this helped for the subsequent sampling of emissions. The parameters monitored were CO, NOx, SO2, using the equipment TESTO 350, having as reference of Book VI, Annex 3, three measurements were made per day depending on the operation of the cauldron from which three representative data were obtained depending on each point of Monitoring. It is important to mention that the comparison of the data obtained was done with TULSMA regulation, Book VI, Annex 3 “Norma de Concentraciones de Emisión al Aire desde Fuentes Fijas de Combustión”; chart 2: Maximum Allowable Limits of Emission Concentrations for Steam Generator Boilers (mg / Nm3), with the result that the monitored parameters are within the allowable limits; Due to constant monitoring of the steam generator.